Information Quality Management in the Malaysian Public Sector: A Preliminary Study on Issues and Challenges - Hassan, Erizamsha; M. Yusof, Zawiyah; Ahmad, Kamsuriah (International Journal of Engineering and Technology, 2018)
Information plays a significant role in enhancing an organizationâ€™s capital, namely as its crucial source of income and a valuable leverage in times of unfavorable economic climate. The strategic management of information, thus, is imperative as it contributes in bringing about success to business by influencing decision-making of the organization for better identification of prospects and to cope with risks. This requires the enhancement of efficiency and effectiveness of information management to expand its readiness and value in decision-making. In spite of its significance, studies in information quality management (IQM), particularly those that investigate issues and challenges, are scarce. This paper, hence, attempts to fill this gap by taking into account both the theoretical and pragmatic approaches in viewing issues and challenges in IQM. In addressing the limited studies in IQM, the paper proposes possible areas of further inquiry for future research. It also seeks to provide a better insight into issues and challenges facing IQM as the studyâ€™s practical impact.Â